PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PUSKESMAS TUNTANG KABUPATEN SEMARANG - Heri Prabowo; Puji Lestari (BBM (Buletin Bisnis & Manajemen), 2019)
The study was done to determine the affect of reliability, responsiveness,assurance, empathy and tangibles either individually or together towards patientsatisfaction. The data that obtained to be processed using descriptive analysis andquantitative statistical analysis. Quantitative analysis used regression analysis to knowthe affect of variable independent towards variable dependent, but before theregression is done, formerly mentioned do the validity test and reliability test alsosettlement test. The result of regression analysis indicate that reliability, responsiveness,assurance, empathy and tangibles give the affect to patient satisfaction really withcorrelation product moment is positive, this case indicates that increasing reliability,responsiveness, assurance, empathy and tangibles will be followed increasing patientsatisfaction, so as well on the contrary. The result of regression analysis test indicatedthat value of F is significant, with correlation as big as 0,813. This case indicates thatreliability, responsiveness, assurance, empathy and tangibles give affect really towardsperformance employee according to together with the connection tightness as big as81,3%.The conclusion that be obtained in this study indicated that to increasing patientsatisfaction, it is necessary to increased reliability, responsiveness, assurance, empathyand tangibles.